Mastectomy Flap Quilting Sutures versus Conventional Dual-Drain Closure for Reduction of Seroma after Modified Radical Mastectomy: Mastectomy Flap Quilting Technique for Reducing Seroma Formation - Choudry, Zafar Ali; Iqbal , Muhammad Saleem; Riaz, Sadia; Ali, Shoukat; Haider, Mussarat; Nadeem, Kashif (Annals of Punjab Medical College, 2026)
Background: Seroma after modified radical mastectomy (MRM) is the most common complication, which is reported to cause longer drainage, delayed wound healing, and higher morbidity in the patient. Objective: To compare the mastectomy flap quilting suture technique versus the conventional mastectomy with respect to seroma formation. Methods: This was a prospective randomized controlled trial of 120 female patients with breast carcinoma at stage II-III who were treated at MRM at Allied Hospital, Faisalabad. The patients were randomly divided into two groups: Group A (60 patients) received quilting sutures and an axillary drain, and Group B (60 patients) received conventional closure and dual drains. Seroma was clinically evaluated at 4-week follow-up and analysed using SPSS v25 (p<0.05). Results: Groups were comparable for age (mean 49.85 ± 6.91 vs. 51.5 ± 5.6 years; p = 0.249), tumour size (4.20 ± 0.91 vs. 4.40 ± 0.85 cm; p = 0.209), stage (p = 0.658), and neoadjuvant chemotherapy (p = 0.854). Seroma was significantly lower in Group A (13.3%) versus Group B (28.3%) (p = 0.043). The benefit was most pronounced in Stage II disease (10.9% vs. 27.1%; p = 0.046) and intermediate-sized tumours 3.5–4.4 cm (5.0% vs. 38.5%; p = 0.008). Conclusion: Quilting sutures are an effective method of reducing post-MRM seroma, especially in Stage II disease and intermediate tumour size. Simple, reliable, and cost-effective, this technique should be performed routinely in MRM, particularly in high-risk patients..